ANALYSIS OF IMPORTANT FEATURES IN THE STRUCTURE OF PHRASEOLOGISMS IN THE GERMAN LANGUAGE - Shukhrathon Imyaminova (Journals Park Publishing, 2023)
This article discusses the analysis of the characteristics of phraseologisms in the German language, the ways in which they are formed morphologically, and the need to pay close attention to the context for understanding the meaning of phraseological units. In addition, it has been pointed out that idiomaticity, polylexicality and stability are characteristic aspects of phraseologisms.
Keywords: суғрориш манбалари; ер ости суви; ҳарорат; сув сарфи режими.